(untitled) (Biological Sciences - PJSIR, 1995)
4,5-Diaryl-5, I-dihydro-s-triazol-3-thiols have been synthesized via cyclization of l-arylaminomethyithio-semi- carbazide derivatives using concentrated hydrochloric acid or from the reaction of arylaminomethylhydrazine deriva- tives with carbon disulphide in alkaline medium. Some heterocyclic system viz, pyrazolidinyltriazoline, thiazolidinyl- aminotriazoline, triazinotriazolidine and tetrazinyltriazoline, have been derived from 3-hydrazinotriazoline derivative, obtained from reaction ofthe title compound with hydrazine. The structures ofthe new compounds have been established by elemental analyses and spectral data.